PRAXICON: INTEGRATING SENSORY, CONCEPTUAL, AND MOTOR SYSTEMS IN A NEW THERAPEUTIC MODEL FOR DEVELOPMENTAL DISABILITIES - Veselin Medenica; Lidija Ivanović (Research in Education and Rehabilitation, 2025)
This paper describes the structure, theoretical background, and the development of Praxicon – Helping Children Build Action Foundations for Daily Functioning and Learning, a new therapeutic model developed by Veselin Medenica and Lidija Ivanović. The model is intended for children with developmental disabilities who have difficulties in imitation, symbolic gesture, and functional tool use. Praxicon, based on Roy’s conceptual-productive model of praxis, integrates the key developmental theories of Vygotsky, Piaget, and Thelen into a structured intervention that targets the perceptual, conceptual, and motor systems. The methodology for describing the intervention follows the TIDieR (Template for Intervention Description and Replication) framework to ensure transparency and replicability. The development process is further supported by the MRC Framework for Complex Interventions, with additional structuring through Intervention Mapping. A logic model depicts the expected pathways of change, linking therapeutic activities to improvements in action planning, symbolic understanding, and functional participation in everyday and school-related tasks. Although the model has not yet been empirically tested, this article provides a comprehensive and systematic narrative of the intervention, highlighting its potential advantages, theoretical coherence, and readiness for feasibility trials. The authors also reflect critically on the model’s limitations and the future steps needed for its validation and implementation.